2022
DOI: 10.1093/jas/skac163
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of twoBacillusprobiotic strains on performance and fecal microbiota of breeding sows and their piglets

Abstract: The effect of long-term administration of two Bacillus strains was tested on 98 breeding sows and their litters allotted into three treatments: a control group (CON); supplemented with 5x10 8 cfu/kg B. subtilis – 541 (BSU); or with 5x10 8 cfu/kg B. amyloliquefaciens – 516 (BAM). Reproductive and performance variables were recorded over three cycles with 56 dams remaining through the third lactation. Blood and fecal samples were taken longitudinally from 12 sows per treatment on days 8 and 21 of the third lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…In the present study, the insignificant effect of probiotic on the number of total born and the number of born alive is corroborated by those found in several previous studies [ 12 , 29 - 32 ]. In contrast, some authors found that the number of total born and the number of born alive in the probiotic groups were higher than those in the untreated groups [ 17 20 , 28 ]. It is clear that probiotic supplementation during late gestation did not have any effects on the number of total born since this parameter was already fixed before probiotic use.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, the insignificant effect of probiotic on the number of total born and the number of born alive is corroborated by those found in several previous studies [ 12 , 29 - 32 ]. In contrast, some authors found that the number of total born and the number of born alive in the probiotic groups were higher than those in the untreated groups [ 17 20 , 28 ]. It is clear that probiotic supplementation during late gestation did not have any effects on the number of total born since this parameter was already fixed before probiotic use.…”
Section: Discussionmentioning
confidence: 92%
“…Several probiotics have been supplemented during different stages of gestation to promote the reproductive performance and health of the sows [12][13][14][15][16], with controversial results. Some probiotics have been shown to increase the number of piglets born alive [17][18][19][20], litter birth weight [19,[21][22][23], and birth weight of piglets [21,24]. On the other hand, some probiotics reduced the birth weight of piglets [13,18,25].…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h of treatment, the continuous treatment samples differentiated more from the control when compared to the daily dose treatment, and this remained true over time ( Figure 2 ). Some studies showed no significant change in beta diversity in the gut microbiota when administrating a Bacillus -based probiotic to swine [ 41 , 43 ], but others did [ 40 , 44 ]. This might be due to the length that the treatments were administered, the mode of administration, or a difference in the product tested.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maternal consumption of a fermented diet protected neonates from colonic inflammation by facilitating the maturation of the gut microbiota and proliferation of gut lactobacillus [ 189 ]. The strong correlations between the microbiota compositions of sows and their offspring are proof of maternal imprinting, which has benefits that persist after weaning [ 190 ].…”
Section: Large Intestinementioning
confidence: 99%